AB0730 Cell cholesterol transport in spondyloarthritides and its response to anti-rheumatic drugs. (15th June 2017) - Ronda, N; Hokstad, I; Deyab, G; Greco, D; Agewall, S; Hjeltnes, G; Whist, JE; Bernini, F; Hollan, I
Abstract : Background: Spondyloarthritis is associated to accelerated atherosclerosis, possibly due to chronic inflammation and lipid metabolism disturbances. Circulating lipoprotein function may be more important than concentration. In particular, cholesterol efflux capacity (CEC) of high density lipoproteins (HDL) opposes to foam cell formation and correlates inversely with cardiovascular risk 1 . Instead, the capacity of low density lipoproteins (LDL) to load cells with cholesterol (CLC) favors atherosclerosis. CEC and CLC may be altered independently from lipoprotein serum levels, e.g. due to chronic autoimmune inflammation or to medical therapies 2 . Objectives: Our aim was to compare CEC and CLC in patients with ankylosing spondylitis (AS) and psoriatic arthritis (PsA). We also aimed to evaluate CEC and CLC modification upon anti-rheumatic therapy and their relationship to lipoprotein levels. Methods: Patients with AS (n=24) and PsA (n=36) were from the observational PSARA study. Treatment was: anti-TNF agents for AS; MTX alone or in combination with an anti-TNF agent for PsA. Serum was drawn before, after 6 weeks and after 6 months of anti-rheumatic therapy to measure CEC with a validated cell model (radioisotopic technique to measure % cholesterol efflux on total cell cholesterol 3 ) and CLC (with a macrophage model and fluorimetric measurement of cell cholesterol 2 ). Results: At baseline serum LDL and total cholesterol were higher in PsA than in AS patients. LDL, total cholesterol and HDL increased after treatment in AS, but not in PsA. In AS, CEC increased after 6 weeks of treatment (4.9±0.3 vs. 5.5±0.3, 95% CI: -1.09 to -0.03, p<0.05), in parallel with HDL serum levels. In PsA, CEC did not differ between any of the time points. CLC did not change with treatment in AS nor in PsA, but was overall higher in PsA than in AS patients. Despite the LDL serum level increase in AS, after 6 months of treatment the difference between CLC in PsA and AS was the most significant (34.0±1.8 in PsA vs 27.8±1.5 in AS, CI 95%: 3.28 to 6.67, p<0.05). In addition, after 6 months of therapy the correlation of CLC with LDL levels, present before treatment, was lost in the AS group. In the PSA group CLC did not correlate with LDL serum levels at any time point. Conclusions: Our novel data indicate that pro-atherogenic lipoprotein dysfunction is more marked, and less responsive to anti-rheumatic treatment, in PsA than AS patients. In AS, CEC improved significantly during anti-TNF therapy, probably due to increase in anti-atherogenic HDL. Despite the LDL increase associated with the anti-TNF therapy in AS patients, CLC stayed constant, standing against a hypothetical pro-atherogenic effect of such LDL increase. These data may be useful for atherosclerosis prevention and treatment with tailored strategies for AS and PsA patients. References: Khera AV, et al. N Engl J Med 364(2):127–35, 2011. Ronda N et al. Arthritis Rheumatol 67(5):1155–64, 2015. Zanotti I et al. Curr Pharm Biotechnol 13(2):292–302, 2012. Disclosure of Interest: None declared